Evaluation rate of aging person based on determination of biological age - V. Fil; I. Kopko; W. Zukow (Kazimierz Wielki University, 2015)
Fil V., Kopko I., Zukow W. Evaluation rate of aging person based on determination of biological age. Journal of Education, Health and Sport. 2015;5(1):125-132. ISSN 2391-8306. DOI: 10.5281/zenodo.14140 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%281%29%3A125-132 https://pbn.nauka.gov.pl/works/529973 http://dx.doi.org/10.5281/zenodo.14140 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.09.2014. Revised 18.01.2015. Accepted: 21.01.2015.   EVALUATION RATE OF AGING PERSON BASED ON DETERMINATION OF BIOLOGICAL AGE   1V. Fil, 1I. Kopko, 2W. Zukow   1Drogobych State Pedagogical University named after Ivan Franko, Drogobych, Ukraine 2Kazimierz Wielki University, Bydgoszcz, Poland   Abstract The article considers the value of biological and passport age of student youth. In experiment participated 140 students aged 17-19 years. Calculated their biological age. Reviewed pace of aging of the body of students. Detected indexes that have the strongest relationship with indicators of biological age. The results compared with researchers of other regions of Ukraine.   Keywords: chronological (passport) age, biological age, appropriate biological age, pulse blood pressure, rate of aging, static balancing, self-reported level of health.